High-performance composite material based on TPU waste recovery and preparation method thereof

By introducing ethylene-acrylate-maleic anhydride terpolymer and modified nano-silica, combined with a twin-screw extruder and a two-stage foaming process, the prepared TPU/EVA composite material achieves a balance between mechanical and elastic properties, solving the problem of difficulty in balancing strength and toughness in traditional methods. This improves the resilience and strength of the material, reduces density, and minimizes environmental pollution and resource waste.

CN121064622APending Publication Date: 2025-12-05NANJING DAMAONIU ENVIRONMENTAL PROTECTION TECH CO LTD +1
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202511364892.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-09-23
Publication Date
2025-12-05

AI Technical Summary

Technical Problem

Existing TPU composite materials have difficulty achieving a balance between mechanical and elastic properties. Traditional methods struggle to balance the performance stability of recycled materials, and TPU waste has a low recycling rate.

Method used

Using TPU waste and EVA particles as the main raw materials, ethylene-acrylate-maleic anhydride terpolymer was added as a compatibilizer, and modified nano-silica was introduced as a reinforcing agent. Modified nano-silica was also introduced as a nucleating agent. The mixture was melt-blended in a twin-screw extruder, and the crosslinking system was added through a side feed port to prepare composite particles. These particles were then foamed, shaped, and cured using a two-step foaming process in a twin-screw extruder to obtain the final composite material. The composite material was then added through a side feed port in a twin-screw extruder.

Benefits of technology

It achieves a perfect balance between mechanical and elastic properties, solves the technical problem of balancing strength and toughness in traditional methods, improves the resilience and strength of materials, reduces density, and reduces environmental pollution and resource waste.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121064622A_ABST
    Figure CN121064622A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of high polymer materials, in particular to a high-performance composite material based on TPU waste recovery and a preparation method of the high-performance composite material. The problem that the mechanical property and the elastic property of an existing TPU composite material cannot be considered at the same time is solved. Recycled TPU waste particles and EVA particles are used as main raw materials, an ethylene-acrylate-maleic anhydride terpolymer is added as a compatilizer, and modified nano silicon dioxide is introduced as a reinforcing and nucleating agent; carrying out melt blending in a twin-screw extruder, and adding a cross-linking system through a side feeding port to prepare composite particles; and carrying out foaming, sizing and curing treatment by adopting a two-stage high-pressure physical foaming process to obtain the final composite material. Through cooperation of multiple components and precise process control, the problem of poor compatibility is solved, and perfect consideration of mechanical properties and elastic properties is realized.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The present application relates to the technical field of high polymer materials, in particular to a high-performance composite material based on TPU waste recycling and a preparation method thereof. BACKGROUND

[0002] Thermoplastic polyurethane (TPU) is widely used in the field of foaming materials such as shoe materials, cushion pads, etc. due to its excellent wear resistance, high resilience and high strength. However, pure TPU foaming material usually has the problem of high hardness and insufficient flexibility, and its melt strength and viscosity are difficult to control during the foaming process, which easily leads to bubble collapse or uneven bubble structure, thereby limiting its application in the field of ultra-light and high comfort.

[0003] However, the existing TPU composite material is difficult to balance the mechanical properties and elastic properties: in order to improve the mechanical strength, rigid fillers or crosslinking agents are often added, but this will lead to an increase in material rigidity and a decrease in resilience and compression permanent deformation performance; on the contrary, in order to optimize the elasticity, flexible copolymers such as ethylene-vinyl acetate copolymer are introduced, but this easily causes phase separation, reduces the overall strength and density balance, and the recycling rate of TPU waste is low, and the performance stability of the regenerated material is difficult to balance by traditional methods.

[0004] Therefore, how to solve the compatibility problem of TPU and EVA, and on this basis, through structure design and process control, to realize the effective balance of the composite material in multiple performance indicators such as low density, high strength and high elasticity, especially to solve the "seesaw" effect between mechanical properties and elastic properties, is the main problem that needs to be solved for the current TPU-based blended foaming composite material.

[0005] Therefore, a high-performance composite material based on TPU waste recycling and a preparation method thereof are provided. SUMMARY

[0006] The present application aims to provide a high-performance composite material based on TPU waste recycling and a preparation method thereof. The present application uses recycled TPU waste particles and EVA particles as the main raw materials, adds ethylene-acrylic acid ester-maleic anhydride terpolymer as a compatibilizer, and introduces modified nano-silica as a reinforcing and nucleating agent; melt blending in a twin-screw extruder, and adding a crosslinking system through a side feeding port to prepare composite particles; then foaming, shaping and curing treatment by two-stage high-pressure physical foaming process to obtain the final composite material. Through multi-component synergy and precise process control, the present application solves the problem of poor compatibility and realizes the perfect balance of mechanical properties and elastic properties.

[0007] To achieve the above-mentioned purpose, the present application provides the following technical solutions:

[0008] The application provides a preparation method of high-performance composite material based on TPU waste recycling, and comprises the following preparation steps:

[0009] TPU particles 60-90 parts, EVA particles 10-40 parts, ethylene-acrylic acid ester-maleic anhydride terpolymer 3-5 parts, modified nano-silicon dioxide 1.5-3 parts, antioxidant 1010 0.5 parts, and zinc stearate 0.3 parts are added into a co-rotating twin-screw extruder (L / D≥40), and the partition temperature of melt extrusion is controlled as follows: the first zone is 160-175 DEG C, the second zone is 170-180 DEG C, the third zone temperature is 180-190 DEG C, the fourth zone temperature is 185-195 DEG C, and the fifth zone temperature is 170-175 DEG C; alpha, alpha'-bis (tert-butyl peroxy) dimethylbenzene 0.3-0.6 parts and triallyl isocyanurate 0.2 parts are added from the side feeding port in the fourth zone, and the screw rotation speed is kept at 300-400 rpm to obtain a melt system; the melt system is cut by a water ring to obtain composite particles with a particle size of 3-5 mm;

[0010] The composite particles are placed in a high-pressure autoclave foaming device, and through two-stage foaming process, the first-stage foaming is heated to 100-120 DEG C, pure nitrogen is injected, the pressure is increased to 20-30 MPa, and the temperature and pressure are kept for 1-2 h; then the pressure is released to atmospheric pressure at a rate of 5-10 MPa / s to induce bubble nucleation; then pure nitrogen is injected again, the second-stage foaming is increased to 10-15 MPa, and the temperature is increased to 140-160 DEG C, and the temperature and pressure are kept for 0.5-1 h to promote stable growth of bubble holes, so that the foaming material is obtained; the foaming material is placed in a mold, the pressure is kept at 5-10 MPa, the temperature is kept at 80-100 DEG C, and the heat setting time is kept for 10-20 min to obtain a setting material; the setting material is placed in a constant temperature box, and the temperature is kept at 50-60 DEG C for 6-12 h to obtain a composite material;

[0011] The modified nano-silicon dioxide is prepared by modifying nano-silicon dioxide with hexamethyldisilazane.

[0012] The TPU particles are obtained by double-shaft tearing and water-cooled vortex milling of TPU foaming waste.

[0013] Preferably, the preparation of the TPU particles comprises the following steps:

[0014] The recycled large-size TPU foaming waste is added into a double-shaft tearing machine, and is broken into TPU fragments with a size less than 50 mm; the TPU fragments are sent into a water-cooled vortex mill, circulating cooling water (10-15 DEG C) is introduced into the outer layer of the grinding cavity, the material is crushed into fine particles with a size of 0.5-2 mm by a high-speed rotating cutter head, the rotation speed is kept at 2000-4000 rpm, and the fine particles are vacuum dried at 80 DEG C for 6-8 h to obtain TPU particles.

[0015] Preferably, the preparation of the modified nanosilica comprises the following steps:

[0016] The nanosilica is dried in a vacuum drying oven at 110-120 DEG C for 4-6h to remove the physically adsorbed water and activate the surface hydroxyl group to obtain dry nanosilica; 100 parts of the dry nanosilica is added into 1000-1500 parts of anhydrous ethanol, stirred and dispersed, and then treated by ultrasonic dispersion for 30-60 min at an ultrasonic power of 200-500 W and an ultrasonic frequency of 20-30 kHz to obtain a uniform and transparent suspension; the suspension is transferred into a three-necked flask, ammonia water is added to adjust the pH to 8-9, the temperature is raised to 60-80 DEG C, and hexamethyldisilazane is slowly added dropwise through a constant pressure dropping funnel under the condition of 200-400 rpm, wherein the mass fraction of the hexamethyldisilazane is 8-12 parts; after the dropwise addition is completed, the modification reaction is carried out for 6-8h to obtain a reaction system; the reaction system is cooled to room temperature, separated and centrifuged for 15-20 min at a centrifugal speed of 8000-10000 rpm, washed with anhydrous ethanol for 3-5 times, and dried in a vacuum drying oven at 60-80 DEG C for 12-20h to obtain the modified nanosilica.

[0017] The application further provides a high-performance composite material based on TPU waste recycling, which comprises TPU particles, EVA particles, ethylene-acrylic ester-maleic anhydride terpolymer, modified nanosilica, antioxidant 1010, zinc stearate, alpha, alpha'-bis(tert-butyl peroxy)dimethylbenzene and triallyl isocyanurate.

[0018] Compared with the prior art, the application has the following beneficial effects:

[0019] 1、The application introduces ethylene-acrylic ester-maleic anhydride terpolymer, the maleic anhydride groups on the molecular chain of which can react with the urethane groups of TPU or form hydrogen bonds, and the ethylene segments have good physical compatibility with EVA, so that a strong interface 'bridge' is formed between TPU and EVA; this greatly improves the compatibility of the two phases, inhibits macroscopic phase separation, and forms a stable interpenetrating network structure; meanwhile, the uniformly dispersed modified nanosilica further improves the strength of the matrix as a physical reinforcing point; the synergistic effect of 'chemical bridging + physical reinforcing' effectively solves the technical problem that the strength and toughness are difficult to be balanced in traditional blending modification.

[0020] 2、The application forms a stable chemical crosslinking network on the basis of the interpenetrating network structure of TPU / EVA in the high-temperature foaming and setting stage through the BIPB / TAIC crosslinking system, which provides strong shape recovery ability for the material. When the material is under pressure, the molecular chain is deformed. The uniform and fine closed cell structure formed by the two-stage foaming process effectively avoids stress concentration and irreversible collapse of the cells. Therefore, the material prepared by the application exhibits higher resilience and lower compression set, which is much better than the system without crosslinking or insufficient crosslinking, and meets the stringent requirements of high-end applications for the elasticity retention rate of the material under long-term cyclic use.

[0021] 3、The application uses nano-silica hydrophobically modified by hexamethyldisilazane, which not only acts as a reinforcing filler, but also acts as an efficient heterogeneous nucleating agent in the high-pressure nitrogen foaming process. The surface energy of the modified nano-particles is reduced, and the compatibility with the polymer melt is good, which can uniformly disperse and induce a large number of rapid nucleation of nitrogen on the surface to form hundreds of millions of tiny bubble nuclei. In addition, the subsequent two-stage foaming process precisely controls the stable growth of these bubble nuclei, and finally forms a uniform, fine and tough cell structure. This "honeycomb-like" microstructure can achieve optimal mechanical support with the least material on a macroscopic level, thereby maintaining ultra-low density while maintaining excellent tensile and tear strength, breaking the inherent cognition that traditional foamed materials have lower strength as the density decreases.

[0022] 4、In the application, the addition of EVA not only gives the material flexibility and adjusts the hardness to the appropriate range, but also reduces the viscosity of the TPU melt, improves the processing fluidity, and makes the nano-filler and crosslinking agent more uniformly dispersed. Secondly, the "nucleation-enhancing" dual-function synergy of modified nano-silica ensures the structural stability and strength at low density. Finally, the "nucleation-growth" precise control synergy of the two-stage foaming process maximizes the foaming efficiency and optimizes the cell morphology. The overall synergy of "component-function-process" enables the application to reduce density and adjust hardness without sacrificing mechanical strength, achieving a balance between mechanical properties and elasticity.

[0023] 5、The application successfully "upcycles" the low-value TPU foaming waste into high-performance lightweight composite materials with better performance than some new materials through blending modification, nano-enhancement and reactive foaming technology, which not only significantly reduces the environmental pollution of waste polymers, saves petroleum resources, but also reduces the raw material cost for enterprises and improves the market competitiveness of products. Compared with the existing technology, the treatment of waste TPU is mostly physical recycling and downgrading or energy recycling, which reduces resource waste and environmental pressure. BRIEF DESCRIPTION OF DRAWINGS

[0024] Figure 1Fig. 1 is a graph of the test results of elongation at break and compression set for Inventive Examples 1-3 and Comparative Examples 1-4. DETAILED DESCRIPTION

[0025] The technical solutions in the embodiments of the present application will be clearly and completely described below with reference to the drawings in the embodiments of the present application. Obviously, the described embodiments are only a part of the embodiments of the present application, rather than all the embodiments. Based on the embodiments in the present application, all other embodiments obtained by a person of ordinary skill in the art without creative work fall within the protection scope of the present application.

[0026] The TPU foaming waste material recycled in the present application is a thermoplastic polyurethane waste material; the particle size of the nano-silicon dioxide is 20-30 nm, and the specific surface area is 200-300 m 2 / g; the EVA particles are ethylene-vinyl acetate copolymer, and the VA content is 18-28%; the BIPB is alpha,alpha'-bis(tert-butyl peroxy)diisopropylbenzene, and the CAS number is 25155-25-3.

[0027] Please refer to Figure 1 The present application provides a high-performance composite material based on TPU waste recycling and a preparation method thereof, and the technical scheme is as follows:

[0028] Example 1

[0029] Preparation of hydrophobically modified nano-silicon dioxide:

[0030] The nano-silicon dioxide was dried in a vacuum drying oven at 120℃ for 6h to remove physically adsorbed water and activate the surface hydroxyl groups to obtain dry nano-silicon dioxide; 100 parts of the dry nano-silicon dioxide was added to 1500 parts of anhydrous ethanol, stirred and dispersed, and then treated by ultrasonic dispersion for 40 min at an ultrasonic power of 300 W and an ultrasonic frequency of 20 kHz to obtain a uniform and transparent suspension; the suspension was transferred to a three-necked flask, ammonia water was added to adjust the pH to 9, and the temperature was raised to 70℃; 10 parts of hexamethyldisilazane was slowly added through a constant-pressure dropping funnel under the condition of 400 rpm; after the addition was completed, the modified reaction was carried out for 6h to obtain a reaction system; the reaction system was cooled to room temperature, separated and centrifuged for 20 min at a centrifugal speed of 8000 rpm, washed with anhydrous ethanol for 5 times, and dried in a vacuum drying oven at 80℃ for 16h to obtain modified nano-silicon dioxide;

[0031] The recovered bulk TPU foaming waste was added into a double-shaft shredder to be broken into TPU fragments with a size less than 50 mm; the TPU fragments were sent into a water-cooled vortex mill, circulating cooling water was passed through the outer layer of the grinding cavity, the material was crushed into fine particles with a size of 2 mm by a high-speed rotating cutter head, the rotation speed was kept at 3000 rpm, and the fine particles were vacuum dried at 80 ℃ for 6 h to obtain TPU particles;

[0032] The TPU particles 70 parts, EVA particles 30 parts, ethylene-acrylate-maleic anhydride terpolymer 4 parts, modified nano-silicon dioxide 2 parts, antioxidant 1010 0.5 parts, and zinc stearate 0.3 parts were added into a co-rotating twin-screw extruder (L / D≥40), α, α'-bis(tert-butyl peroxy)diisopropylbenzene 0.5 parts and triallyl isocyanurate 0.2 parts were added from the side feeding port in the four zones, and the screw rotation speed was kept at 400 rpm to obtain a molten system; the molten system was cut into composite particles with a particle size of 4 mm by a water ring cutter;

[0033] The composite particles were placed in a high-pressure kettle foaming device, heated to 120 ℃, injected with pure nitrogen, pressurized to 20 MPa, and kept at temperature and pressure for 2 h; then the pressure was released to atmospheric pressure at a rate of 8 MPa / s to induce bubble nucleation; then pure nitrogen was re-injected, pressurized to 12 MPa, and heated to 150 ℃, and kept at temperature and pressure for 1 h to promote stable bubble growth to obtain a foaming material; the foaming material was placed in a mold, kept at a pressure of 8 MPa and a temperature of 100 ℃, and shaped for 20 min to obtain a shaped material; the shaped material was placed in a constant temperature oven and aged at 60 ℃ for 8 h to obtain a composite material.

[0034] Examples 2-4 were prepared according to the preparation method and parameters of Example 1, with the differences shown in Table 1.

[0035] Table 1 Parameter changes of Examples 1-4

[0036]

[0037] Comparative Example 1 was prepared according to Example 1, with the difference that no EVA particles were added, and 100 parts of TPU particles were used.

[0038] Comparative Example 2 was prepared according to Example 1, with the difference that no ethylene-acrylate-maleic anhydride terpolymer was added, and the amounts of the other components remained unchanged.

[0039] Comparative Example 3 was prepared according to Example 1, with the difference that no BIPB was added, and the amounts of the other components remained unchanged.

[0040] Comparative Example 4 was prepared according to Example 1, with the difference that BIPB was added through the main feeding port, and the other steps remained unchanged.

[0041] Comparative Example 5 refers to Example 1, except that no modified nano-silica is added, and the amounts of other components remain unchanged.

[0042] Comparative Example 6 refers to Example 1, except that no modification treatment is performed on the nano-silica, and the nano-silica is added.

[0043] Experimental Example 1: Mechanical property test

[0044] The composite materials prepared in Examples 1-4 and Comparative Examples 1-6 are subjected to mechanical property test. The tensile strength and elongation at break are tested according to GB / T6344-2008, with a tensile speed of 50 mm / min. The tear strength is tested by delamination tear test, using a trouser-shaped sample, with a unit of kN / m. The specific test results are shown in Table 2.

[0045] Table 2: Test results of examples and comparative examples

[0046]

[0047]

[0048] It can be seen from the results of Table 2 that the composite obtained by adjusting the components in Comparative Examples 1-6 shows significantly reduced mechanical properties compared to the examples; comparing the results of Examples 1-4, it can be seen that with the change of the amount of TPU and EVA, the mechanical properties of the composite change significantly, a small amount of EVA as a flexible particle dispersed in the TPU matrix can be well combined with the matrix under the action of the compatibilizer to play a certain toughening effect, but it does not change the nature of the material dominated by TPU performance; with the increase of the amount of EVA, the volume of the dispersed phase also increases, and under the action of the compatibilizer and the crosslinking agent, the system forms a stable interpenetrating network structure; however, with too high EVA content, the phase structure of the system begins to change, EVA changes from the original dispersed phase to TPU as a continuous phase, and even becomes the main continuous phase, and the performance of the material is dominated by the relatively weak and soft EVA, which leads to a decrease in mechanical properties; it can be seen from the results of Comparative Example 1 that EVA mainly acts as a flexible modifier and a foaming aid in this system, which can effectively reduce the hardness of TPU material and improve the flexibility of the material, while the lack of synergistic effect of EVA affects the resilience and compression resistance; in Comparative Example 2, the lack of ethylene-propylene-acrylic acid ester-maleic anhydride terpolymer leads to the phase separation of TPU and EVA, forming a coarse "sea-island" structure, and the interface separation is serious, which cannot effectively transfer stress when stressed, and the interface becomes a defect point, leading to the destruction of the material under very low stress; in Comparative Examples 3-4, without adding BIPB, only linear macromolecular physical entanglement occurs during the melt blending of TPU / EVA, and during the foaming and setting process, high temperature will intensify the movement and slip of molecular chains, and the system cannot form a stable three-dimensional network structure, and the strength and dimensional stability of the material completely depend on the van der Waals force between molecular chains, so the mechanical properties decrease significantly; adding BIPB with all materials from the main feeding port will cause it to decompose before the material is fully plasticized and uniformly mixed, leading to premature crosslinking, and due to uneven crosslinking, some areas are crosslinked excessively and some areas are crosslinked insufficiently, leading to a decrease in overall mechanical properties; it can be seen from the results of Comparative Examples 5-6 that nano-silicon dioxide has a very high specific surface area, and its surface can be well combined with the polymer matrix after hydrophobic modification, and these nano-particles as physical crosslinking points can effectively limit the movement of polymer chains, thereby improving the overall mechanical properties of the material; however, unmodified silicon dioxide is completely incompatible in the matrix and will form agglomerates due to its surface energy, which not only cannot play a reinforcing role, but also becomes a stress concentration point in the material, affecting the mechanical properties.

[0049] In summary, in the present application, high elasticity and wear-resistant matrix are provided by TPU, EVA imparts flexibility and low density, the compatibilizer bridges the interface of TPU / EVA to form an interpenetrating network, and the crosslinking system generates a free radical network structure at high temperature to improve the mechanical properties; the modified nano-silica acts as a nano-nucleating agent and reinforcing agent, and the hydrophobic surface ensures uniform dispersion; the chemical network provides a "skeleton", the physical network fills and provides reinforcement, and a three-dimensional network structure is constructed, so that the mechanical properties of the material are improved.

[0050] Examples 5-7 were prepared according to the preparation method and parameters of Example 1, with the differences shown in Table 3.

[0051] Table 3 Parameter changes of Example 1, Examples 5-7

[0052]

[0053] Comparative Example 7 was prepared according to Example 1, with the difference that only one foaming process was used instead of two foaming processes.

[0054] Comparative Example 8 was prepared according to Example 1, with the difference that only two foaming processes were used instead of two foaming processes.

[0055] Comparative Example 9 was prepared according to Example 1, with the difference that no maturation treatment was performed.

[0056] Comparative Example 10 was prepared according to Example 1, with the difference that no pressure relief to atmospheric pressure and re-pressurization was performed.

[0057] Comparative Example 11 was prepared according to Example 1, with the difference that no modified nano-silica was added, and no EVA particles were added, and 100 parts of TPU particles were used.

[0058] Experimental Example 2 Density and Hardness Test

[0059] The composite materials prepared in Example 1, Examples 5-7, Comparative Example 1, and Comparative Examples 5-11 were respectively subjected to density and hardness tests, the Shore C hardness of the composite materials was tested according to GB / T 2411-2008, and the density of the composite materials was tested using GB / T 6343-2009, and the specific test results are shown in Table 4.

[0060] Table 4 Density and hardness test results of examples and comparative examples

[0061]

[0062]

[0063] From the results of Table 4, it can be seen that in the comparative examples, the density and hardness of the obtained composite material cannot achieve effective balance, and the overall performance is reduced; in Comparative Example 1, the addition of EVA particles leads to an increase in the overall rigidity of the material, and the high proportion of TPU particles makes the cell structure dense, making it difficult to form a uniform low-density foaming structure, thus increasing the density and hardness; from the results of Comparative Examples 5-6, it can be seen that the modified nano-silica enhances the interfacial compatibility with the polymer matrix through hydrophobic modification, promotes cell nucleation and stabilization, reduces the density and increases the hardness; the absence of modified nano-silica leads to uneven cell nucleation, reduced cell wall strength, increased material density, and decreased hardness; in addition, the unmodified nano-silica has strong hydrophilicity on the surface, poor compatibility with the hydrophobic polymer matrix, and easy agglomeration, leading to uneven dispersion, affecting the uniformity and stability of the cell structure; in Comparative Examples 7-8, the one-stage foaming process only controls the nucleation process without secondary control of cell growth, resulting in too small cell size and failing to achieve the best density reduction effect, and the uneven distribution of cell size leads to a decrease in overall performance; direct cell growth lacks the high-pressure decompression nucleation process of the first stage, resulting in insufficient bubble nucleation, making the number of internal cells in the final foam small and the size large, the density reduction not obvious, and the hardness also relatively high; from the results of Comparative Example 10, it can be seen that the lack of decompression process prevents nitrogen from rapidly precipitating from a supersaturated state to form a large number of bubble nuclei in a very short time, resulting in a small number of internal cells in the final foam, a non-obvious density reduction, and a relatively high hardness; from the results of Comparative Example 9, it can be seen that the curing process is a key step for eliminating internal residual stress and stabilizing the crosslinked network structure; without curing, although the density and hardness may be similar to those of the examples at the initial test, the internal structure of the material is unstable and is prone to dimensional changes after long-term use or stress; in Comparative Example 11, the absence of the compatibilizing and toughening effect of EVA and the nucleation enhancing effect of modified nano-silica makes it impossible to improve the processability and foaming effect of the material, and the balance of the overall density and hardness is destroyed.

[0064] In summary, the present application uses modified silica as an efficient heterogeneous nucleating agent in the high-pressure foaming process, inducing rapid nucleation of the physical foaming agent on the particle surface to form a large number of uniform and fine cells; at the same time, the nano-silica as a reinforcing filler can appropriately improve the hardness of the material, and its dual role ensures that the hardness of the material is effectively controlled and improved while the density is reduced; at the same time, the addition of EVA reduces the viscosity of the TPU melt, improves the processing performance, and makes the nano-filler and crosslinking agent better dispersed; under the synergistic effect of the two-stage foaming process, the foamed body has an ideal microstructure, ensuring low density while obtaining excellent hardness. The present application realizes the perfect balance of low density and appropriate hardness through the synergistic effect of nucleation and hardness adjustment of modified nano-silica, hardness adjustment and processing of EVA and TPU, and precise control of the two-stage foaming process.

[0065] Elasticity performance test of experimental example 3

[0066] The composite materials obtained in examples 1-4 and comparative examples 1-6 were subjected to elasticity performance test, the compression permanent deformation of the composite material was tested according to GB / T 6669-2008, the deformation recovery ability of the composite material after being kept at a certain compression ratio and temperature for a certain time was removed; the percentage rebound value was calculated by measuring the rebound height of the pendulum or weight falling freely from a certain height according to GB / T 6670-2008; the test results are shown in Table 5. Figure 1 The test results of the elongation at break and compression permanent deformation of examples 1-3 and comparative examples 1-4 of the present application are shown in the following figures.

[0067] Table 5: Elasticity performance test results of examples and comparative examples

[0068] Example Compression set / % Percentile resilience / % Example 1 18.3 72.6 Example 2 32.3 73.8 Example 3 24.4 69.1 Example 4 22.2 73.5 Comparative Example 1 32.8 55.2 Comparative Example 2 32.5 60.3 Comparative Example 3 52.6 50.8 Comparative Example 4 38.6 59.3 Comparative Example 5 37.5 56.8 Comparative Example 6 45.2 52.6

[0069] From Table 5, Figure 1The results show that, in the comparative examples, the resilience of the composite material is significantly reduced compared to the examples; in Comparative Example 1, the lack of toughening effect of EVA, the high melt viscosity of pure TPU, the poor processing fluidity, the non-uniform microstructure of the material, the increased rigidity of the cell structure, and the weakened elastic recovery ability; the blending of TPU and EVA can form a more uniform and flexible interpenetrating network structure, improving the overall resilience of the material; in Comparative Example 2, the lack of ethylene-propylene-acrylic acid ester-maleic anhydride terpolymer leads to weakened interfacial bonding between components, decreased uniformity and stability of the cell structure, and affected elastic recovery; the compatibilizer can improve the interfacial compatibility between TPU, EVA and modified nano-silica, and promote uniform dispersion of the components; in Comparative Example 3, the lack of crosslinking agent leads to the lack of stable chemical crosslinking network between polymer molecular chains, and after compression, the molecular chains cannot quickly recover to the original state through the crosslinking points, resulting in increased permanent compression deformation; the results of Comparative Example 4 show that the addition of BIPB through the side feeding port can accurately control the crosslinking reaction time during melt extrusion, avoiding premature crosslinking leading to unstable extrusion; when BIPB is added through the main feeding port, the crosslinking reaction may occur in the early stage of extrusion, affecting the fluidity of the melt system and the uniformity of the cell structure, and reducing the overall elastic performance; in Comparative Examples 5-6, the lack of modified nano-silica leads to the lack of effective nucleating agent during foaming, the small number and large size of the cells, the inability to form a fine and uniform cell structure, the inability to uniformly disperse stress during stress, the occurrence of local collapse or permanent deformation in some areas, and thus the increase in permanent compression deformation and the decrease in resilience; the unmodified nano-silica has poor compatibility with the polymer matrix and is prone to agglomeration, which not only cannot act as an effective nucleating point, but also forms stress concentration points in the material, which seriously affects the elasticity and resilience of the material and also leads to a decrease in mechanical properties.

[0070] In summary, the present application uses BIPB as a crosslinking agent to form a chemical crosslinking network to provide restoring force; uses modified nano-silica as a nucleating agent to optimize the micro-foaming structure, and adds EVA to improve the processing performance and melt fluidity of TPU, so that the crosslinking agent and modified nano-silica can be better dispersed in the polymer matrix, and the synergistic effect of the three can be utilized to obtain a composite material system with good mechanical properties and elastic performance.

[0071] Although embodiments of the present application have been shown and described, it will be understood by those skilled in the art that various changes, modifications, substitutions and alterations can be made therein without departing from the principles and spirit of the application, the scope of which is defined by the appended claims and their equivalents.

Claims

1. A method for preparing high-performance composites based on TPU waste recycling, characterized by: The preparation method comprises the following steps: The TPU particles, EVA particles, ethylene-acrylate-maleic anhydride terpolymer, modified nano-silica, cross-linking agent and auxiliary agent are added into a co-rotating twin-screw extruder to melt extrude a melt system; and the melt system is cut into composite particles by water ring cutting; The composite particles are foamed by a two-stage foaming process to obtain a foamed material; the foamed material is heat set to obtain a set material; and the set material is aged to obtain the composite material; The modified nano-silica is prepared by modifying nano-silica with hexamethyldisilazane; The TPU particles are obtained by crushing TPU foaming waste by a double-shaft shredder and a water-cooled vortex mill.

2. The method according to claim 1, wherein, The cross-linking agent comprises α, α'-bis (tert-butyl peroxy) dimethylbenzene and triallyl isocyanurate; the auxiliary agent comprises antioxidant 1010 and zinc stearate; and the cross-linking agent is added into the melt extrusion through a side feeding port.

3. The method according to claim 1, wherein the method is characterized by, The preparation of the TPU particles comprises the following steps: The recycled TPU foaming waste is added into a double-shaft shredder to crush into TPU fragments; the TPU fragments are sent into a water-cooled vortex mill, circulating cooling water is supplied to the outer layer of the grinding cavity, and the rotating cutter disc crushes the material into fine particles; and the fine particles are dried in a vacuum to obtain the TPU particles.

4. The method according to claim 1, wherein, The preparation of the modified nano-silica comprises the following steps: The nano-silica is dried in a vacuum to obtain dried nano-silica; the dried nano-silica is added into anhydrous ethanol, stirred and dispersed, and then treated by ultrasonic dispersion to obtain a suspension; The suspension is transferred into a three-necked flask, ammonia water is added to adjust the pH to alkaline, the hexamethyldisilazane is added dropwise under heating and stirring, a reaction system is obtained by modification reaction; the reaction system is cooled to room temperature, separated and centrifuged, washed with anhydrous ethanol, and dried in a vacuum to obtain the modified nano-silica.

5. The method according to claim 1, wherein the method is characterized by, The two-stage foaming process comprises the following steps: The composite particles are foamed in the first stage, and then depressurized to atmospheric pressure at a rate of 5-10 MPa / s; pure nitrogen is re-injected, the pressure is increased to 10-15 MPa in the second stage foaming, and the temperature is increased to 140-160 ℃ to obtain the foamed material.

6. The method according to claim 1, wherein the method is characterized by, The heat setting treatment and the aging treatment comprise the following steps: The foamed material is placed in a mold to obtain the set material by heat setting; and the set material is placed in a thermostat to obtain the composite material by aging at 50-60 ℃ for 6-12 h.

7. A high performance composite based on TPU waste recycling, characterized by, The raw materials of the composite material comprise TPU particles, EVA particles, ethylene-acrylate-maleic anhydride terpolymer, modified nano-silica, antioxidant 1010 and zinc stearate, α, α'-bis (tert-butyl peroxy) dimethylbenzene and triallyl isocyanurate; and the composite material is prepared by the preparation method of any one of claims 1-6.

Citation Information

Cited By

  • High-elasticity foaming material capable of realizing closed-loop regeneration foaming and preparation method of high-elasticity foaming material

    CN121554918A